The Effect Of Sodium Fluoride Administration On Il-1β And Tnf-α Expression On Orthodontic Teeth Movement - Sutjiati, Rina (Health Notions, 2022)
Introduction: Relapse in post orthodontic treatment is common in the community because resorption in the pressure side occurs excessively due to teeth being moved with an orthodontic device. Excessive resorption can be inhibited by using NaF which has been shown to inhibit osteoclast activity, thereby reducing osteoclast numbers. The purpose of this study was to analyze the effect of NaF administration on IL-1β and TNF-α expression of osteoclast in orthodontic teeth movement. Methods: Animal model using 16 male Wistar rats given orthodontic force using NiTi closed coil spring adjusted to give 10 grams/cm2 of mechanical strength, were applied to the palatal in the maxillary incisors of the Wistar rat teeth. Rats were divided into two groups, the control group (C group) and treatment group (T group) given topical NaF application (11.75 ppm). Immunohistochemical examination was performed to calculate IL-1β and TNF-α expression on osteoclasts on the 7th day and 14th day. Results: The administration of NaF reduces IL-1β and TNF-α osteoclast’s expression both on the 7th day (p